2006
DOI: 10.1111/j.1600-0889.2006.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Water vapour <sup>18</sup>O/<sup>16</sup>O isotope ratio in surface air in New England, USA

Abstract: A B S T R A C T In this paper, we report the results of the analysis of two high-resolution time-series of water vapour 18 O/ 16 O ratio (δ v ) in surface air observed in Connecticut, USA. On an annual time-scale, δ v is a linear function of ln w, where w is water vapour mixing ratio, and is approximated by a Rayleigh distillation model with partial (80%) rainout. On time scales a few days, δ v shows considerable variations, often exceeding 20 per mil, and is higher in the wetting phase than in the drying phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
152
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(179 citation statements)
references
References 37 publications
24
152
3
Order By: Relevance
“…In addition, the latest instruments are of a reasonably small size and power consumption is low, allowing for the application of this technique to in-situ measurements (Lee et al, 2005;Gupta et al, 2009;Sturm and Knohl, 2010;Aemisegger et al, 2012). Notably, Lee et al (2006) have reported continuous δD water vapor records for New England, USA, for a period of one year, using a tunable diode laser (TDL) spectroscopy system. However, because of instrumental nonlinearity, drifting signal, dependence on water vapor concentration, temperature sensitivity, and pressure variations in the absorption cell, regular and frequent calibration with a water vapor standard of known isotope content is required for longterm field observations.…”
Section: N Kurita Et Al: Evaluation Of Water Vapor Isotope Analyzermentioning
confidence: 99%
“…In addition, the latest instruments are of a reasonably small size and power consumption is low, allowing for the application of this technique to in-situ measurements (Lee et al, 2005;Gupta et al, 2009;Sturm and Knohl, 2010;Aemisegger et al, 2012). Notably, Lee et al (2006) have reported continuous δD water vapor records for New England, USA, for a period of one year, using a tunable diode laser (TDL) spectroscopy system. However, because of instrumental nonlinearity, drifting signal, dependence on water vapor concentration, temperature sensitivity, and pressure variations in the absorption cell, regular and frequent calibration with a water vapor standard of known isotope content is required for longterm field observations.…”
Section: N Kurita Et Al: Evaluation Of Water Vapor Isotope Analyzermentioning
confidence: 99%
“…Such a correlation could result from the case of simple Rayleigh rainout processes, where condensation phases progressively remove water from the atmosphere and deplete the remaining atmospheric vapour in heavy isotopes (Dansgaard, 1964;Lee et al, 2006;Wen et al, 2010). The progressive rainout follows a temperature decrease, and should also result in a correlation between δ v and T , and subsequently between rainfall isotope content (δ p ) and T , which has led to the establishment of the isotopic thermometer (Dansgaard, 1964;Jouzel et al, 1997).…”
Section: Correlations Between Isotope Data and Local Climatic Parametersmentioning
confidence: 99%
“…Whereas cryogenic trapping provides grab samples generally averaging a couple of hours, laser spectrometry performs continuous high frequency (up to ∼ 1 Hz) measurements of δ v (Kerstel and Gianfrani, 2008). This technology offers new insights into processes that affect the isotopic composition of atmospheric water vapour and the number of studies based on continuous ground level isotope measurements over multiweek periods is continuously increasing, either using a tunable diode laser (TDL) (Lee et al, 2006;Wen et al, 2010Wen et al, , 2012Griffis et al, 2011;Welp et al, 2012), off-axis integrated cavity output spectroscopy (OA-ICOS) (Sturm and Knohl, 2010;Sunmonu et al, 2012;Farlin et al, 2013;SteenLarsen et al, 2013) or wavelength-scanned cavity ring-down spectroscopy (WS-CRDS) Tremoy et al, 2012;Steen-Larsen et al, 2013. Among these experiments are some low latitude studies which have focused on the tracing of tropical or subtropical convective activity in West Africa (Tremoy et al, 2012) or in South America .…”
Section: Introductionmentioning
confidence: 99%
“…4c, Table 2). During precipitation events, the water vapour generally maintains a state of equilibrium with falling raindrops (Lee et al, 2006). During heavy precipitation events, the isotope ratios of water vapour and condensate decrease as saturated air rises, because of continued fractionation during condensation (Gedzelman and Lawrence, 1982), and the δ 18 O values of precipitation tend to become more depleted ( Fig.…”
Section: The Effects Of Meteorological and Environmental Factors On δmentioning
confidence: 99%